Prevalence of cervical intraepithelial neoplasia and hpv induced lesions in the lower Genital tractof HIV seropositive/aids women - Fialho, Susana C.A.V.; Almeida, Gutemberg L.; Maldonado, Paula M.; Vai, Isabel do; Andrade, Angela V.C. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Introduction: the totality of notification in Brazil until 2002 is 237.588 and lhe number of HIV infected women is the importam fact in the HIV epidemic. Objective: lo study the prevalence of cervical intraepithelial neoplasia and HPV induced lesions in HIV seropositive/AIDS women. the distribution of these lesions in lhe lower genital tract and its degrees, correlating them with the CD* + T lymphocyte count. Methods: in this study. 130 HIV infected women cases have been analyzed from may 1998 to october 2000, with directed biopsy of the lower genital tract, evaluating the distribution of the lesions and its degrees with the CD* + T lymphocyte count. Results: lhe prevalence of CIN was 30% and C1N I was the main histologic degree. The histologic degree increased with lhe reduction of the CD* + T lymphocyte count. except for CIN III. The pure HPV infection was the rnain finding in the histopathological examination of the vagina, vulva and perianal region with 64.9%, 87,2% and 81.1%, respectively. The main site of infection of the HPV was the vulva (34.0%) and of the intraepithelial neoplasias was the uterine cervix (79,5%). Conclusion: there was a high prevalence of CIN among the cervical intraepithelial neoplasias. the CIN I was the main histopathological finding, the impact of the immunosupression influenced the histopathological degrees. excepted CIN III. the main site of the intraepithelial neoplasias was the uterine cervix and of the HPV induced lesions. lhe vulva, and in both sites the lesions tended to be unicentric.